Vibration Effects of Nonclassically Damped Building-Piping Systems Subjected to Extreme Loads - YongHee Ryu; WooYoung Jung; BuSeog Ju (Shock and Vibration)
Piping leakage can occur at T-joint, elbows, valves, or nozzles in nuclear power plants and nonnuclear power plants such as petrochemical plants when subjected to extreme loads and such leakage of piping systems can also lead to fire or explosion. For example, leakage of sodium, toxic gases, or nitrogen in hospitals can cause man-made hazards. The primary objective of this research is to understand the vibration effects due to classical/nonclassical damping with building-piping systems under extreme loads. The current evaluation employed finite-element analysis to calculate the effects of the responses of classically and nonclassically damped building-piping systems. Classical and nonclassical damping matrices for a coupled primary-secondary system were developed based on the Rayleigh equation. A total of 10 selected ground motions were applied to single degree of freedom (SDOF) primary-SDOF secondary (2-DOF coupled) systems in which the ratios of the natural frequencies between the primary and secondary systems ranged between 0.9 and 1.1. It revealed that the vibration effect of nonclassical damping was significant where the natural frequencies of the two systems were nearly tuned. For piping-material nonlinearity, the effects of nonclassical damping on the result forces of piping systems were not significantly different from those of classical damping.